Soil Property Data for Four Africa RISING Sites in Ethiopia - International Center for Tropical Agriculture (International Food Policy Research Institute, 2019)
The data included in this study were collected to assess the health of the soil at four Africa RISING sites: Basona, Michew, Jawe, and Sinana. The data were collected following land degradation surveillance framework (LDSF) whereby within a 10km by 10km sites, we considered 16 clusters of 1km by 1km and within each cluster we have 0.1 ha plots, within which 0.01 ha subplots were located for sampling. International Center for Tropical Agriculture (CIAT) led the data collection.